PERUBAHAN NAMA ZONA EKONOMI EKSKLUSIF INDONESIA DI LAUT CINA SELATAN MENJADI LAUT NATUNA UTARA (1982-2017) - Yovindra Satria Maulana; Bedriati Ibrahim; Bunari (Nusantara Hasana Journal, 2023)
This research aims to describe the events behind the change of name of Indonesia's exclusive economic zone in the South China Sea to the North Natuna Sea and its impact from a historical perspective. This research uses the historical method with Miles and Huberman analysis techniques. The results of this study reveal that China made claims to the SCS based on historical claims prior to the 1982 UNCLOS which were unilateral in nature and caused conflicts and violations of Indonesia's sovereign rights in the SCS, causing Indonesia to react by changing the name of the EEZ in the SCS to the North Natuna Sea in 2017.